Perceptions of Graduate Students at the University of São Paulo about Plagiarism Practices in Academic Works - MARCELO KROKOSCZ; SUELI M.S.P. FERREIRA (Anais da Academia Brasileira de Ciências, 2019)
Abstract: Our objective was to identify the understanding of theoretical aspects and the interpretation of practical situations that a sample of 3,623 graduate students (Population = 22,438) at the University of São Paulo (Brazil) have regarding academic plagiarism. The survey used an electronic questionnaire containing 30 multiple choice questions developed from the literature concerning the concept and definition of plagiarism, occurrence modality, types of plagiarism, reasons for occurrence, standards and preventive actions adopted. We identified that the fact of respondents agreeing or disagreeing with the theoretical-conceptual characteristics of plagiarism did not make a difference in their capacity of correctly assessing practical situations characterizing plagiarism. Moreover, the agreement or disagreement responses regarding the concepts of plagiarism were observed not to differ among the respondents who had been trained to use references and citations. However, the same respondents correctly interpret practical situations characterizing plagiarism. Therefore, this study suggests that there is a gap between theoretical and practical knowledge regarding plagiarism for graduate students. Although the technical training related to the correct use of research sources is an important prerequisite in the capacity-building process, it does not seem to be enough to prevent plagiarism practices.